Educational paradoxes in the twentieth century. Work and memory of Giuseppe Prezzolini (1882-1982) among the United States, Italy, and Switzerland - Petruzzi, Carmen (Historia y Memoria de la Educación, 2022)
The essay analyzes the articles by Giuseppe Prezzolini published in Paradossi educativi 1914-1964 (Armando 1964) relating to Italian school reforms, educational models and curricula. Despite his long absence from Italy, journalist Giuseppe Prezzolini continued to monitor the changes in Italian schools from afar, enriching the contemporary debate with his sharp overseas observations. Furthermore, through his work it is possible to advance the historical-educational construction of the Italy that was changing and, across the Atlantic, of the transformation of the mindset of Italian-American families. In the year of the fortieth anniversary of his death we remember, through his own words, a remarkable figure who lived, wrote and commented on the great events of the twentieth century.